Advances in the Renin-Angiotensin-Aldosterone System: Relevance to Diabetic Nephropathy. (2008) - Koitka, Audrey; Tikellis, Christos
Abstract : Hypertension is now recognized as a key contributory factor to the development and progression of kidney disease in both type 1 and type 2 diabetes. The renin angiotensin system (RAS) and its effector molecule angiotensin II, in particular, have a range of hemodynamic and nonhemodynamic effects that contribute not only to the development of hypertension, but also to renal disease. As a result, therapeutic inhibition of the RAS with angiotensin-converting enzyme inhibitors and/or selective angiotensin II type 1 receptor blockers has been proposed as a key strategy for reducing kidney damage beyond the expected effects one would observe with blood pressure reduction per se. Although the relationship between the RAS and the progression of diabetic renal disease has been known for many decades, recent advances have revealed a more complex paradigm with the discovery of a number of new components. Thus, further understanding of these new components of the renin angiotensin aldosterone system (RAAS), such as the angiotensin type 2 receptor subtype, angiotensin converting enzyme 2, and the recently cloned renin receptor, is likely to have therapeutic implications for disorders such as diabetic nephropathy, where interruption of the RAAS is widely used.